The users' perspectives towards the role of public libraries in bridging the digital divide in Ngaka Modiri Molema District - Modiba, Mashilo Thomas (My University, 2016)
This study investigated the users‟ perspective of the role played by public libraries in bridging the digital divide in the rural-urban communities with specific reference to Ngaka Modiri Molema District libraries, in the North-West Province, South Africa. The research methodology utilized in this study is a descriptive survey in design and quantitative in nature, through a questionnaire as a data collection tool, distributed to hundred (100) library users selected through quota, convenience and accidental sampling methods. Twenty (20) library users belonging to each of the five public libraries in the district participated in the study. It is revealed that public libraries in the Ngaka Modiri Molema District are playing a significant and crucial role in bridging the digital divide. This is due to the fact that the library users have indicated that they are able to conduct research, send and receive e-mails; they are able to type their personal and academic documents and even play computer games with the library computers and the internet. Based on these findings, this study recommends that district municipalities and the provincial government should continue to provide the public libraries with computers connected to the internet to all the libraries in Ngaka Modiri Molema District and to train the public librarians to be able to impart computer skills to the communities. Public librarians should also initiate computer orientation courses to provide basic skills to those who are computer illiterate in the communities.
Thesis ((M.A. (Information Studies)) -- University of Limpopo, 2016
Keywords: Public libraries; Digital divide; Internet access; Computers; Public libraries -- South Africa--North West; Digital divide -- South Africa -- North West; Public access computers in libraries; Libraries and the Internet -- South Africa -- North West